Dopant activity for highly in-situ doped polycrystalline silicon: hall, XRD, scanning capacitance microscopy (SCM) and scanning spreading resistance microscopy (SSRM). (18th March 2021) - Coq Germanicus, Rosine; Lallemand, Florent; Chateigner, Daniel; Jouha, Wadia; Moultif, Niemat; Latry, Olivier; Fouchet, Arnaud; Murray, Hugues; Bunel, Catherine; Lüders, Ulrike
Abstract: Progressing miniaturization and the development of semiconductor integrated devices ask for advanced characterizations of the different device components with ever-increasing accuracy. Particularly in highly doped layers, a fine control of local conduction is essential to minimize access resistances and optimize integrated devices. For this, electrical Atomic Force Microscopy (AFM) are useful tools to examine the local properties at nanometric scale, for the fundamental understanding of the layer conductivity, process optimization during the device fabrication and reliability issues. By using Scanning Capacitance Microscopy (SCM) and Scanning Spreading Resistance Microscopy (SSRM), we investigate a highly in situ doped polycrystalline silicon layer, a material where the electrical transport properties are well known. This film is deposited on a oxide layer as a passivating contact. The study of the nano-MIS (SCM) and nano-Schottky (SSRM) contacts allows to determine the distribution and homogeneity of the carrier concentration (active dopants), especially by investigating the redistribution of the dopants after an annealing step used for their activation. While the chemical analysis by Secondary Ions Mass Spectroscopy (SIMS) quantifies only the dopant concentration in the polycrystalline layer, the comparison with macroscopic characterization techniques as Hall effect measurements, supported with XRD characterization, shows that careful SCM and SSRM measurements can be used to highlight the dopant activation. This analysis gives a complete investigation of the local electrical properties of the passivating contact when the parameters (applied voltages and applied forces) of the AFM nano-contacts are correctly controlled.